Venice and Nearby Antiquity: The Antique Pula and the Renaissance Art - Gudelj, Jasenka (Array, 2010)
The paper explores the Renaissance interest for the beautifully preserved antiquities of Pula, a small town in venetian Istria on the maritime route to the East, through the cultural practice of interpreting, imitating, copying, emulating or quoting antique models. The Roman buildings of Pula served as models for monuments as important as Porta dell’Arsenale in Venice and Aragonese arch in Naples, thus opening series of questions on circulation and reception of “provintial” or “Venetian” antiquity, and on defining the set of cultural references to the absent original. The transmission of the antique forms occurred through various media, connected with an oscillation of denotation that in some cases even changed the perception of the model itself. The study of this type, as the title suggests, is strongly indebted to Patricia Fortini Brown’s writings on Venetian sense of the past, as Pula is one of the Serenissima’s “nearby places of the distant past”.